Upside-down stomach – results of mini-invasive surgical therapy - Cestmir Neoral; Lenka Zbrozkova; Katherine Vomackova; Rene Aujesky; Radek Vrba (Videosurgery and Other Miniinvasive Techniques)
Aim: The authors evaluate the results of mini-invasive therapy in patients diagnosed with upside-down stomach. Material and methods: From 1998 to 2008, a total of 27 patients diagnosed with upside-down stomach were surgicallytreated at the 1st Department of Surgery, University Hospital Olomouc. Before the operation, patients wereexamined endoscopically and a barium swallow was performed. In all 27 patients (100%), the operation was performedelectively laparoscopically. The principle of the operation in all cases was reposition of the stomach into theabdominal cavity, resection of the hernial sac and hiatoplasty. In addition, in 15 patients (56%) with reflux symptomsor endoscopic findings of reflux oesophagitis, fundoplication in Nissen’s modification was also performed. Fundopexywas indicated in 12 patients (44%). Results: In all patients (100%), the operation was performed mini-invasively; conversion to an open procedure wasnever necessary. In 3 cases (11%), the left pleural cavity was opened during the operation; this was treated by introducinga chest drain. The operation mortality in the patient set was zero; morbidity was 11%. A year after the operation,patients were re-examined, and follow-up endoscopy and barium swallow were performed. Conclusions: In all patients diagnosed with upside-down stomach, surgical treatment is indicated due to the risk ofdeveloping severe complications. Mini-invasive surgical therapy in the hands of an experienced surgeon is a safe procedurewhich offers patients all the benefits of mini-invasive therapy with promising short- and long-term results.